PENINGKATAN KEMAMPUAN MENGIDENTIFIKASI SIFAT-SIFAT BANGUN RUANG MELALUI PENERAPAN CONTEXTUAL TEACHING AND LEARNING SISWA KELAS V SDN BATUBELAH TIMUR - Asnawi Asnawi (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2018)
Research using a Class Action Research. The research subjects were students of class V SDN East Batubelah Subdistrict of 20 students. Individual circumstances of students is quite diverse aspects of cognitive, affective and psychomotor. Results showed that student learning outcomes after the implementation of Contextual Teaching and Learning in grade students of SDN Batubelah Eastern District of Year 2017 can be achieved significantly higher after implementing intensive measures in accordance with procedures specified learning. In the previous cycles is known that the percentage of the value of mastery is achieved is 30% increased by about 60% so that the percentage of classical completeness in this cycle to 90%. The average value of the class also increased the plume. In previous cycles the average grade achieved was 63. In this cycle the value of the average grade achieved was 80. Then there was an increase of about 17 points. And the average value of the class in this cycle has demonstrated the value above minimum completeness criteria (KKM) with both criteria.